2007
DOI: 10.1111/j.1463-1326.2007.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of ApoB and ApoA1 measurements to cardiovascular risk assessment

Abstract: LDL has been widely recognized as the major atherogenic lipoprotein and designated as the primary target for prevention of coronary heart disease (CHD); however, there is growing evidence that other triglyceride-rich lipoproteins, such as very low-density lipoprotein (VLDL) and intermediate density lipoprotein (IDL) carry atherogenic potential as well. This led to the designation of non-HDL cholesterol (HDL-C) (LDL + IDL + VLDL) as a secondary target of treatment for hyperlipidaemia. As each one of LDL, IDL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 86 publications
5
44
0
1
Order By: Relevance
“…In our study, LDL-C and Apo B levels were significantly decreased, as indicated in the Atorvastatin Comparative Cholesterol Efficacy and Safety Study after 3 months of statin therapy (20). HDL-C and Apo A1 levels did not change because statins have fewer effects on Apo A1 in patients with hypercholesterolemia (20). In some studies it was shown that statin treatment increased Lp(a) levels (21,22), but in some studies controversial effects were reported, as in ours (23,24).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In our study, LDL-C and Apo B levels were significantly decreased, as indicated in the Atorvastatin Comparative Cholesterol Efficacy and Safety Study after 3 months of statin therapy (20). HDL-C and Apo A1 levels did not change because statins have fewer effects on Apo A1 in patients with hypercholesterolemia (20). In some studies it was shown that statin treatment increased Lp(a) levels (21,22), but in some studies controversial effects were reported, as in ours (23,24).…”
Section: Discussionsupporting
confidence: 68%
“…In our study, LDL-C and Apo B levels were significantly decreased, as indicated in the Atorvastatin Comparative Cholesterol Efficacy and Safety Study after 3 months of statin therapy (20). HDL-C and Apo A1 levels did not change because statins have fewer effects on Apo A1 in patients with hypercholesterolemia (20).…”
Section: Discussionsupporting
confidence: 56%
“…ApoB-containing particles in excess can lead to atherogenecity since apoB is the molecule mainly responsible for the oxidization of LDL, a key step in the atherogenic process. ApoA-I is crucial for the reverse cholesterol transport, since it enables esterification of cholesterol and promotes the externalization of excess cholesterol in peripheral cells to HDL (Andrikoula & McDowell, 2008;Walldius & Jungner, 2004).…”
Section: Abstract: Swedish Twins Heritability Cvd Biomarkersmentioning
confidence: 99%
“…Increased triglyceride concentration was associated with a reduced HDL/apo A-1 ratio suggesting that a relatively modest increase in triglycerides may rapidly alter the relative cholesterol content of HDL and thereby apo A-. 22,23 Mutation in apolipoprotein A-1 with a single amino acid replacement may form dimeric complexes and this may restrict HDL size and cause HDL deficiency. 24 In the present study, higher values for HbA1c are obtained in case of poor metabolic control and persistent hypoglycemia and this might have contributed to complications such as CAD in diabetic cases.…”
Section: Discussionmentioning
confidence: 99%